Laporan Kasus: Melanoma Maligna pada Gingiva Regio Mandi-bulla - Luh Putu Iin Indrayani Maker; Moestikaningsih . (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2014)
Primary oral malignant melanoma is a very rare case (0.2-8%), and because of it’s hidden location and asymptomatic, it was often found at a late stage. This kind of case was never been reported in the past 10 years in Denpasar. Malignant melanoma, especially the pigmented variant, was easily diagnosed from histopathology specimen. But many variations occurred, and could be mistaken with nevus (nevoid melanoma) or mesenchymal spindle cell tumour, so immunohistochemistry examination is needed to confirmed it. In certain cases, cell block from FNAB aspirate material could help the patient to spent a lower cost to get a diagnostic material, considering the possibility of using immunohistochemistry procedure from cell block material. The case that we reported here was clinically, Radiologic, FNAB, histopathologically and immunohistochemistry for HMB45 and S100 from cell block was confirmed the primary malignant melanoma of right gingival mandible with a late stage. Key words : cell block, FNAB, histopathology, immunohistochemistry, malignant melanoma